Case Report: Frontoparietal Metastasis From a Primary Fallopian Tube Carcinoma - Jang, Anthony I.; Bernstock, Joshua D.; Segar, David J.; Distasio, Marcello; Matulonis, Ursula; Bi, Wenya Linda (Frontiers in Surgery, 2021)
Background: Metastatic brain tumors typically arise from primary malignancies of the lung, kidney, breast, skin, and colorectum. Brain metastases originating from malignancies of the female genital tract are extremely rare. We present a case of fallopian tube brain metastasis and in so doing review the pertinent literature. Case description: We describe a 59-year-old patient with a history of fallopian tube carcinoma who presented with an incidentally identified left frontal brain mass. MRI demonstrated an enhancing lesion in the left centrum semiovale with a second enhancing lesion noted in the cerebellar vermis. She underwent a left parietal craniotomy for resection of the dominant and clinically symptomatic lesion. Immunohistochemical stains were positive for PAX8 and p53, confirming fallopian tube origin. Conclusions: Fallopian tube cancer brain metastasis is extremely uncommon. We highlight the treatment and surgical resection of this patient’s BRCA1 metastatic fallopian lesion and systematically review the literature regarding the pathogenesis, diagnosis, treatment and histologic characteristics of the previously identified fallopian tube metastases to the central nervous system. The optimal course of treatment for brain metastasis of fallopian tube carcinoma has not been clearly defined due in part to the rarity of this condition. Consistent with BRCA1 neoplasms involving the breast and ovaries, the BRCA1 status of the patient’s primary tumor likely increased the risk of central nervous system dissemination. This highlights a potential benefit of early screening of individuals with metastatic gynecologic malignancies associated with BRCA1 in the absence of any neurological symptoms.